PENGARUH KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN, KELEMAHAN SISTEM PENGENDALIAN INTERNAL, KEPATUHAN PERATURAN PERUNDANG-UNDANGAN, STATUS DAERAH DAN UKURAN DAERAH TERHADAP OPINI LAPORAN KEUANGAN PEMERINTAH DAERAH DI PULAU JAWA TAHUN 2013 - Samsul Rosadi; Yudi Siyamto; Helti Nur Aisyiah (ITB AAS INDONESIA Surakarta, 2017)
This study aims to examine the effect of timely delivery of financial statements, weaknesses of internal control systems, compliance with statutory regulations, regional status and size of the region on the opinion of local government financial reports on the island of Java. By using LKPD 110 the city / regency government in Java Island. Sampling technique is purposive sampling, that is how to determine sample by using certain criterion. Hypothesis testing techniques using logistic regression analysis. The results of this study indicate that the variable timeliness of financial reporting, weakness of the internal control system, compliance with legislation has a negative effect on the opinion of local government financial statements. While the variables of regional status and size of the regions have no effect on the opinion of local government financial statements.